Anti-windup scheme of the electronic load sensing pump via switched flow/power control. (August 2019) - Cheng, Min; Zhang, Junhui; Xu, Bing; Ding, Ruqi; Yang, Geng
Highlights: The actual test shows a windup problem of the electrohydraulic load sensing pump. A switched flow/pressure control scheme is proposed to achieve anti-windup. The advantages are simper structure and stability property of the overall system. The proposed controller has been successfully validated with a hydraulic excavator. Abstract: The electronization demand of hydraulic systems is more and more urgent to improve the automation level of mobile machinery. The hydro-mechanical variable displacement pumps are being replaced increasingly by electronically controlled pumps to integrate flow control, power limitation and other functions flexibly. However, this paper discloses that the flow/power control requirements bring about an integral windup problem for the existing PID pump controller. Accordingly, an anti-windup switched flow/power controller is proposed to address this problem. The switched controller introduces a flow matching method to replace the electronic load sensing (ELS) controller, while a power controller with dynamic compensation is utilized to achieve power limitation. The mathematical model of the control system is established. The stability of the switched control system is discussed through the linearization model. Especially, the system stability when switching between the flow/power modes is proven by the describing function method. Boom motion tests with a 2-ton hydraulic excavator are implemented to validate the proposed controller. The test results indicated that the proper pump flow was supplied to achieve desired load velocity, and also the system power was limited within the setting range. Moreover, performance deterioration caused by integral windup is avoided thoroughly compared with the existing ELS controller. The comparison tests also show the limitation of traditional anti-windup methods.